PENYELENGGARAAN EVENT CAR CLINIC MEGUIARS INDONESIA DALAM MEMBANGUN MEREK - Mokhammad Naigam Mahriva; Eka Wenats Wuryanta (Jurnal Pustaka Komunikasi, 2020)
The purpose of this research is to find out more about how an event Car Clinic Meguiars Indonesia is organized so that it is able to build a brand on Meguiars Indonesia as a vehicle paint company. In this study using a descriptive qualitative approach to the paradigm of cosntructivism and using the case study method. The concept in this research is brand, brand building and brand audits. From the results of the study stated that Meguiars Indonesia managed to become the top of mind audience because the brand is easy to remember. The success of being the top mind was also supported because the implementation of an event that could have an impact on the target audience. Events are indeed made with the aim of engaging the target audience in programs organized by the company and this is what drives an event to be a memorable and more motivating experience because the target audience participates and becomes a part of the event.